Sagittal spinal-pelvic alignment in patients with Crowe type IV developmental dysplasia of the hip - Peng Ren (BMC Musculoskeletal Disorders, 2020)
Abstract Background The impact of high dislocated dysplastic hips on spinal-pelvic alignment has not been well described. This study aims to evaluate compensatory spinal radiographic changes and presence of back pain in patients with Crowe type IV developmental dysplasia of the hip (DDH). Methods An observational study was conducted from July 2016 to December 2017, and 49 consecutive patients with Crowe IV DDH were enrolled. Forty-nine sex- and age-matched asymptomatic healthy adults were recruited as the controls. The sacral slope (SS), lumbar lordosis (LL), spino-sacral angle (SSA), C7 tilt (C7T), and sagittal vertical axis (SVA [C7]) were measured on lateral whole spine radiographs. The presence of low back pain and visual analogue scale (VAS) scores were recorded. Results The patients with Crowe IV DDH showed significantly greater SS (47.5 ± 7.5° vs. 40.4 ± 6.7°, p < 0.05), LL (− 63.7 ± 9.2° vs. − 53.3 ± 11.5°, P < 0.05), SSA (141.8° ± 7.2° vs. 130.6 ± 7.9°, p < 0.05), C7T (93.9 ± 3.6° vs. 91.1 ± 3.7°, P < 0.05), and lower SVA(C7) (− 16 mm[− 95–45] vs. 6.4 mm[− 52–47], p < 0.05) compared to the controls. The patients with bilateral Crowe IV DDH also exhibited larger SS, LL, SSA, and C7T and a smaller SVA (C7) than those with unilateral Crowe IV DDH. Sixty-three percent of the patients with Crowe IV DDH reported low back pain. Conclusion The patients with Crowe IV DDH exhibited abnormal spinal-pelvic alignment characterized by anterior pelvic tilt, lumbar hyperlordosis, and a backward-leaning trunk. Bilateral Crowe IV DDH had a greater impact on spinal-pelvic alignment than unilateral Crowe IV DDH.